2017
DOI: 10.1016/j.sna.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A novel force sensing platform using passive magnetic springs for mechanical characterisation of human oocytes

Abstract: This article presents a novel low cost force sensing platform for the mechanical characterisation of human oocytes. This platform is compatible with the specific context of Assisted Reproductive Technology (ART). The oocyte is placed inside a standard Petri dish filled with a culture medium. It is immobilized using a holding pipette. The disposable parts used to mechanically test each oocyte are made of glass. This configuration is very similar to the one used in IntraCytoplasmic Sperm Injection protocol excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…20,21 Thus, the mechanical characterizations can be used for oocyte selection. 22 In a recent study, Yenez et al found that there is a difference between the viscoelastic properties of viable and nonviable fertilized oocytes. 23 They also demonstrated that the mechanical stiffness of mouse embryo is a decisive criterion for detecting embryo quality.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…20,21 Thus, the mechanical characterizations can be used for oocyte selection. 22 In a recent study, Yenez et al found that there is a difference between the viscoelastic properties of viable and nonviable fertilized oocytes. 23 They also demonstrated that the mechanical stiffness of mouse embryo is a decisive criterion for detecting embryo quality.…”
mentioning
confidence: 99%
“…24,25 A nanoforce sensor and a new force sensing platform using passive magnetic springs were presented to measure mechanical characteristics of oocytes. 22,26 It should be pointed out that these studies require complex equipment and are dependent on the experimental environment. 22,26 More recently, the genetic screening method was reported to optimize oocyte development rate and embryo quality.…”
mentioning
confidence: 99%
See 3 more Smart Citations